How to save the wounded self: Power distance belief's moderation of self‐identity threat and status‐related consumption. Issue 1 (18th November 2019) - Cui, Hong‐jing; Fam, Kim‐Shyan; Zhao, Tai‐yang; Xu, Wei; Han, Cheng
Abstract: There is ample evidence in the relevant literature to show that self‐identity threat affects consumers' behavior, psychological needs, purchasing behavior, and product choice. The present research takes self‐identity threat to another level with a focus on the moderating role of power distance belief (PDB) in the relation to self‐identity threat and status consumption. The research involves two studies. Study 1 shows that threatened participants with a high PDB prefer status goods to nonstatus goods. By contrast, the low‐PDB group is indifferent to the status of goods. Study 2 reexamines the results of Study 2 with different participants and goods and tests the moderated mediation of symbolic compensatory need in the status consumption of high‐PDB participants. The results and implications of our findings are presented in the Discussion section.